The face-to-face provokes wisdom of love Levinas' ethical view on knowledge and truth - Burggraeve, Roger (2020)
In a "loving struggle" with the often-misunderstood phenomenology of the 'Face,' Roger Burggraeve critically explicitates how Levinas how Levinas goes beyond Husserl's notion of "the intentionality of consciousness." In a first movement, Burggraeve points out the paradoxical "epiphenomenality" of the Face. It is beyond perception and representation. Unlike the I who discloses the meaning of the Other, the Face as "epiphany" makes meaning arise before the I and reveals itself as the origin of meaning. The Face escapes the images and ideas of the I. Here, Levinas speaks of "exteriority" not as "spatial distance" but as absolutely different. In a second movement, Burggraeve deepens the positive meaning of the Face as expression and revelation. An Absence in its presence, the Face is an "expression of the invisible by the visible" through the glance and the word of the Other. In this sense, the Face of the Other teaches the I something incredibly new. Escaping the grasp of the I and forever a surprise, the Face obliges the I to listen to a new meaning of knowledge and truth based on ethical responsibility. in a third movement, the Face manifest its radical alterity. Absolute experience is not disclosure but revelation. The Face arouses "a traumatism of astonishment" to promote the Wisdom of Love which is spelled out as respect, ethical responsibility, and justice for the Other. Only then is there beyond recognition, a true acknowledgement of the Other.
Keywords: Levinas, Emmanuel; Epiphany; Ethics; Truth